Factors and optimizations of healthcare workers' perception in alternative care facilities - Wang, Hao; Luo, Peng; Wu, Yimeng; Zeng, Xianqi (Frontiers in Public Health, 2022)
Background Diverse measures have been carried out worldwide to establish Alternative Care Facilities (ACFs) for different ends, such as receiving, curing or isolating patients, aiming to cope with tremendous shock in the urban medical system during the early passage of the COVID-19 epidemic. Healthcare workers always felt anxious and stressed during multiple major public health emergencies in medical facilities. Some active measures to improve healthcare workers' perceptions, such as temporary training, workflow improvement, and supplementary facilities, were proved insufficient in several past public health emergencies. Therefore, this study aims to analyze the contributing factors of the healthcare workers' perceptions of the ACFs in this pandemic, which can help find an innovative path to ensure their health, well-being and work efficiency. Method This paper conducted semi-structured in-depth interviews with the world's first batch of healthcare workers who have worked in ACFs through a qualitative study based on Grounded Theory. The healthcare workers interviewed from Heilongjiang, Shandong, Fujian, and Hubei provinces, have worked in one of the four different ACFs built in Wuhan. The results are obtained through the three-level codes and analyses of the interview recordings. Results The factors affecting the perception of healthcare workers in ACFs during the epidemic situation can be summarized into five major categories: individual characteristics, organization management, facilities and equipment, space design, and internal environment. The five major categories affecting the composition of perception can be further divided into endogenous and exogenous factors, which jointly affect the perception of healthcare workers in ACFs. Among them, individual characteristics belong to endogenous factors, which are the primary conditions, while other categories belong to exogenous factors, which are the decisive conditions. Conclusion This paper clarifies factors affecting the perception of healthcare workers in ACFs and analyzes the mechanism of each factor. It is posited that the passive strategies are a promising solution to protect healthcare workers' health, improve their work efficiency, and help reduce the operation stress of ACFs. We should train multidisciplinary professionals for future healthcare and enhance collaborations between healthcare workers and engineers. To sum up, this paper broadens new horizons for future research on the optimization of ACFs and finds new paths for alleviating healthcare workers' adverse perceptions of ACFs.